Permanent Deformation Evaluation of Modified Asphaltic Pavement Based on Numerical Simulation Models - Alhelyani Akram; Zhang Shuwen (Civil and Environmental Engineering, 2023)
Since the use of additives supplies the different properties required to develop better-performing roadways, modification with additives has been used as one of the attractive alternatives when the base asphalt does not satisfy the requirements for traffic load, climate variations, and paving structure. This study evaluates the effect of additive materials of improving the ability of the surface layer to withstand permanent deformation. In addition, it discusses to what extent using waste materials as additive materials affects permanent deformation resistance and the extent of using waste materials as alternative modifiers to commercial polymers to enhance permanent deformation resistance. In this study, the simulation using the ABAQUS program under the conditions of using different percentages of the additives, changes in the thickness of the surface layer, and increasing the temperature on permanent deformation of the asphalt layer was investigated. The simulation results showed that using modified mixtures improved the Hot Mix Asphalt HMA's properties and decreased the mixtures' temperature susceptibility, which manifested as a decrease in permanent deformation (lower rutting depth) when compared to an unmodified mixture. Furthermore, using waste materials led to the greatest decrease in permanent deformation among all models.